PENGARUH KEPEMIMPINAN, MOTIVASI TERHADAP KINERJA KARYAWAN MELALUI SEMANGAT KERJA SEBAGAI VARIABEL INTERVENING PADA PT. PERKEBUNAN NUSANTARA IV REGIONAL III KEBUN SEI BUATAN KABUPATEN SIAK PROVINSI RIAU - Fadia Mahmuatul Rofikoh; Sri Indarti; Syapsan Syapsan (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study positions employee performance as the dependent variable, reflecting the level of individual success in carrying out tasks according to their responsibilities. Employee performance is influenced by various organizational factors, including leadership and motivation, with work enthusiasm serving as the intervening variable. The selection of these variables is based on key relevant theories, namely Transformational Leadership Theory (Bass), Herzberg’s Two-Factor Theory, and Expectancy Theory (Vroom), which conceptually explain how leadership and motivation can foster work enthusiasm and, in turn, improve employee performance. The research objects are all permanent employees at the core/plasma plantation unit of PT Perkebunan Nusantara IV Regional III Kebun Sei Buatan, with a total population of 105 employees. The sampling technique used is Proportionate Stratified Random Sampling, and the number of employee samples in each unit was determined using the proportional formula, resulting in 84 respondents. This study employs a quantitative descriptive method, using primary data obtained through questionnaires and secondary data from company documents. Data analysis was conducted using the Partial Least Squares (PLS) approach to examine both direct and indirect effects among variables. The results indicate that leadership has a positive and significant effect on employee performance, meaning that the better the leadership style applied, the higher the employee performance achieved. Motivation also has a positive and significant effect on employee performance, suggesting that intrinsic and extrinsic drives can enhance work productivity. Work enthusiasm has a positive effect on employee performance, indicating that higher work enthusiasm leads to better work outcomes. In addition, leadership and motivation have a positive effect on work enthusiasm, showing that managerial support and motivational factors can foster employee enthusiasm. The mediation analysis results further reveal that work enthusiasm mediates the relationship between leadership and motivation toward employee performance, although the indirect effect is smaller than the direct effect.